Electrochemical performance of polymer-derived SiOC and SiTiOC ceramic electrodes for artificial cardiac pacemaker applications. Issue 6 (15th March 2021) - Jang, Jongmoon; Warriam Sasikumar, Pradeep Vallachira; Navaee, Fatemeh; Hagelüken, Lorenz; Blugan, Gurdial; Brugger, Juergen
Abstract: In an implantable electrode, such as a pacemaker electrode, fibrotic tissue formation due to a foreign body reaction is an important challenge affecting the efficiency to transmit the electrical signal of the device. The chemical inertness, biocompatibility, and electrical conductivity of polymer-derived ceramics (PDCs) are promising features in terms of overcoming this challenge. Here, the electrochemical behavior of polymer-derived silicon oxycarbide (SiOC) and titanium-doped SiOC (SiTiOC) ceramic electrodes for use as pacemaker electrodes is investigated by measuring impedance spectroscopy and cyclic voltammetry. In addition, typical stimulation electrodes such as iridium oxide, titanium nitride, platinum, and glassy carbon were prepared and loaded simultaneously into a custom-made electrochemical testing platform for comparison with SiOC and SiTiOC electrodes under identical conditions. The SiOC and SiTiOC electrodes shows a wide electrochemical stability window in the range of −0.9 to 1.2 V with a double layer capacitance as the charge injection mechanism at the electrode/phosphate-buffered saline interface. Also, analyzing the voltage transient shows that the maximum charge injection of the SiTiOC electrode was about 28 μC/cm 2 . The results of the electrochemical evaluation and comparison of SiOC and SiTiOC stimulating electrodes will be helpful to understand fundamental characteristics for the potential of this material as candidate for next-generation pacemaker electrodes.